2019
DOI: 10.1111/apa.14977
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of self‐reported pain in childhood cancer survivors

Abstract: Aim The aim of this systematic review was to examine the frequency and risk factors of pain among long‐term childhood cancer survivors based on self‐reported questionnaire studies. Participants aged 21 years or younger at the time of their cancer diagnosis were included. Methods The Medline (OVID), PubMed and PsycINFO databases were searched for manuscripts published between January 1, 1990, and August 31, 2018, following the PRISMA statement for reporting systematic reviews. Results In total, 25 studies, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
(434 reference statements)
0
7
1
Order By: Relevance
“…Previous studies have reported pain prevalence rates in survivors of childhood cancers ranging from 4.3% to 75%. 9,11 Our finding of 70% is a liberal estimate of those who reported some degree of pain in the previous month. We also found that 15% of participants experienced pain frequently (ie, often or almost always) over the previous month, pointing towards those for whom pain may be more problematic and impactful.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Previous studies have reported pain prevalence rates in survivors of childhood cancers ranging from 4.3% to 75%. 9,11 Our finding of 70% is a liberal estimate of those who reported some degree of pain in the previous month. We also found that 15% of participants experienced pain frequently (ie, often or almost always) over the previous month, pointing towards those for whom pain may be more problematic and impactful.…”
Section: Discussionmentioning
confidence: 65%
“… 3 , 13 In a previous report, bodily symptoms triggered fears of recurrence in 62% of young survivors, sometimes many years after finishing cancer treatment. 1 Because pain is emerging as an especially worrisome symptom, and given growing evidence that a sizable number of childhood cancer survivors report persistent and frequent pain, 9 , 11 it may be particularly important to address pain-related worries within childhood cancer survivorship care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although survival rates for childhood cancer are high, an estimated 66-88% of long-term survivors will have one or more chronic health conditions (Phillips et al, 2015), supporting the fact that interest in CAM use extends beyond the initial treatment period. For example, the prevalence of pain as a long-term effect of cancer in childhood cancer survivors (CCS) is estimated to be between 10 and 59% (Reinfjell & Zeltzer, 2019) and identifying as a minority, unemployed, and/or as being single were associated with reporting pain in adult long-term survivors of childhood cancers, which in turn predicts CAM use (Lu et al, 2011). Many CCS continue to use CAM to relieve prolonged symptoms of fatigue, pain and anxiety and to improve overall health and fitness (Ndao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…6 Pain prevalence among adult survivors of childhood cancer ranges from 10% to 59%. 7 In a study including 10 397 cancer survivors and 3034 sibling controls, pain in the past week related to the history of cancer was reported by 21% of adult survivors of childhood cancer at an average of 17 years after cancer diagnosis. 8 Acute or chronic pain in cancer survivors may occur as late effects after chemotherapy, particularly if neuropathic agents had been used.…”
Section: Introductionmentioning
confidence: 99%